Empreendedorismo e inovação: um estudo junto aos servidores do Instituto de Ciências Agrárias da UFMG - Nivea Alves de Almeida (2016)
The broad objective of this dissertation was to perform an applied study on the basis of an entrepreneurial and innovative practice in an Academic Unit of the Federal University of Minas Gerais (UFMG) located in Montes Claros city, Minas Gerais, in order to allow the absorption and incorporation of principles associated with entrepreneurship in its innovative feature, to contribute to the establishment and strengthening of partnerships between the University and the regional business sector, to promote the articulation of innovative projects capable of contributing to the regional development and to establish mechanisms that will allow the organizational levels to act with a more entrepreneurial behavior. As methodological strategy, it was adopted a qualitative descriptive research in a UFMG unit with education administrative technicians and teachers as reference group acting and allocated in the campus while the research was done. Data collection took into consideration primary evidences, whose main source was the questionnaires applied to the employees from the Agrarian Sciences Institute (ICA). The main result of this studywas the establishment of 14 (fourteen) actions chosen to comprise a possible "Innovation Plan" for the context and which are related directly to the characteristics of the profile of the studied sample, with actions considered effective and capable to generate results according to the employees themselves and also with the characteristics of the organizational environment in the respondents point of view. Therefore, this dissertation generates a subsidy that can be used by leaders and people interested in the theme and may allow the structuring of local actions, enabling Montes Claros Campus to contribute to the macro organizational objective of UFMG linked to Innovation and Entrepreneurship and also to support further studies aimed at adding information to the research efforts and instruments of this study, attempting to improve the interpretative and explanatory capacity of those who study and practice innovation and entrepreneurship in public organizations.